Exploring outcomes for children who have experienced out-of-home care in Western Australia. - Lima, Fernando (International Journal of Population Data Science, 2018)
Introduction Children who have been in out-of-home care have faced significant issues during their lives, and they are considered one of the most vulnerable groups in society. Given the limited evidence in Western Australia about outcomes for care-leavers, this study represents a base line for future studies of care-leavers outcomes. Objectives and Approach A retrospective cohort study exploring the outcomes for young people born between 1990-1995, who have reached at least 18 years of age and have had a period of care, compared to other similar children in WA. This project used administrative linked data from the Department of Communities Child Protection and Family Support Division, Departments of Health, Education, and Corrective Services. This study undertook a descriptive approach to compare outcomes for young people who have left out-of-home care, and logistic regression modelling to explore the odds of having poorer outcomes among those who had a period in care. Results Young people aged 18 years and over who had been in out-of-home care had worse outcomes compared to controls. Care-leavers had nearly twice the hospital admission rate of those who never had contact with the child protection system, almost three times more likely to have a mental health related contact, less likely to achieve a high school completion certificate and attend University, and more likely to have a juvenile community sentence or adult detention. A group of young people who had a period in care were identified as more likely to have ‘poorer outcomes’ compared to the rest of the Care group if they: were Aboriginal; female; born in a more disadvantaged area; and first entered care after the age of 10. Conclusion/Implications Young people who have been in care are at high risk of a range of poor outcomes, even compared to other children who have experienced similar disadvantage. Regardless of the causes, it is incumbent upon the State as acting ‘parents’ to provide the best possible support to improve their outcomes.